Redefining the partnership: A study on non‐equity partners - Vandenhaute, Marie‐Laure; Hardies, Kris (Contemporary Accounting Research, 2025)
Abstract Over the past decade, the audit profession has significantly increased its use of non‐equity partners for private (non‐listed) company audits. Such partners lead audit engagements and sign audit reports but do not share in the partnership's profits. Non‐equity partner positions were introduced in response to increasing workloads and to retain talented individuals unsuited to or uninterested in equity partnership, either temporarily or permanently. Using data from Big 4 private company audits during the period 2008–2017, our analyses show that equity incentives affect auditors' reporting behavior and their clients' financial reporting quality. Non‐equity partners are less likely to issue going‐concern opinions to their financially distressed clients, their reporting is less accurate (i.e., more Type II errors), their reporting is less conservative, and their clients' financial reporting is of lower quality (i.e., more frequent reporting of small earnings increases and more tax restatements). We also find that equity incentives mitigate some of the negative effects of fee‐based compensation on auditors' reporting behavior. Moreover, our findings suggest that incentives arising from ownership, rather than partners' innate differences or client differences, drive these associations.